2023
DOI: 10.1186/s12876-023-02832-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein intake and mortality among survivors of liver cirrhosis: a prospective cohort study

Abstract: Background Liver cirrhosis is a worldwide burden and is associated with poor clinical outcomes, including increased mortality. The beneficial effects of dietary modifications in reducing morbidity and mortality are inevitable. Aim The current study aimed to evaluate the potential association of dietary protein intake with the cirrhosis-related mortality. Methods In this cohort study, 121 ambulatory cir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The exact mechanisms by which DAL may influence cirrhosis and its complications are currently unclear. However, several factors may contribute to this association, such as insulin resistance (IR) 24 , hypertension (HTN) 25 , high consumption of red meat 26 , and low consumption of fruits and vegetables 27 . It has been demonstrated that high acid-load diets can cause chronic low-grade metabolic acidosis (MA), which is associated with metabolic abnormalities 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact mechanisms by which DAL may influence cirrhosis and its complications are currently unclear. However, several factors may contribute to this association, such as insulin resistance (IR) 24 , hypertension (HTN) 25 , high consumption of red meat 26 , and low consumption of fruits and vegetables 27 . It has been demonstrated that high acid-load diets can cause chronic low-grade metabolic acidosis (MA), which is associated with metabolic abnormalities 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reducing red meat consumption may slow the progression of NAFLD and fibrosis, as continued red meat consumption was linked to a higher risk of hepatic fibrosis 60 . Additionally, the study by Daftari et al 26 demonstrated that lower intakes of animal protein are associated with lower mortality risks in patients with cirrhosis. On the other hand, consuming potassium-rich foods, such as fruits and vegetables, may favor muscle preservation, while acidosis may impair protein synthesis, increase proteolysis, and enhance amino acid oxidation, leading to a greater loss of muscle mass 61 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver cirrhosis is the terminal stage of most chronic liver diseases (CLDs), having the highest incidence and mortality among liver-related diseases, which has an inferior prognosis [ 1 , 2 , 3 ]. In 2019, LC was associated with 2.4% of global deaths, and cirrhosis deaths are predicted to increase over the next decade, with the rate gradually increasing in some countries [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It eventually leads to liver regeneration and fibrogenesis, enhances collagen and extracellular matrix deposition, and gradually progresses to cirrhosis [ 6 , 10 ]. Cirrhosis gives rise to numerous systemic complications, including ascites, malnutrition, sarcopenia and various others [ 3 , 5 , 11 ]. Malnutrition is a prominent characteristic and a significant complication of cirrhosis.…”
Section: Introductionmentioning
confidence: 99%